A comprehensive review on grapes (Vitis spp.) cultivation and its crop management - Abhijit Khadatkar; Chetankumar Prakash Sawant; Deepak Thorat; Ajita Gupta; Swapnaja Jadhav; Dhananjay Gawande; Ajit Prahlad Magar (Discover Agriculture)
Abstract Grapes (Vitis vinifera) are extensively grown in tropical and sub-tropical climate for its wine as well as direct consumption as table grapes or raisin. Grape production substantially contributes to the economy of smallholder farmers of developing countries. Despite the relevance of grape production in the international market and the potential for boosting rural economy, the automation in grape production is very low. Mechanization in grapevine cultivation is an indispensable factor for timely operations and cost-savings. Therefore, the technological interventions for grapes production as well as its management in vineyards have been reviewed in the paper. Vineyards are undergoing a gradual transformation into a mechanized way with the advent of newer and ready to adopt technologies like planting, pruning, weeding, spraying, fertilizer application, irrigation and harvesting. However, selective in nature, some operations are still carried out manually like pruning, weeding, and harvesting in developing countries. Although complete mechanization is possible for each production and cultivation process tedious and labor-consuming practices must be prioritized for mechanization and automation. This review systematically summarizes the existing technologies and explores the future prospects for researchers to automate grapevine production and crop management technology for grapevine cultivation.